2018
DOI: 10.1038/s41593-018-0141-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal atlas of the dorsal horn defines its architecture and links sensory input to transcriptional cell types

Abstract: The dorsal horn of the spinal cord is critical to processing distinct modalities of noxious and innocuous sensation, but little is known of the neuronal subtypes involved, hampering efforts to deduce principles governing somatic sensation. Here we used single-cell RNA sequencing to classify sensory neurons in the mouse dorsal horn. We identified 15 inhibitory and 15 excitatory molecular subtypes of neurons, equaling the complexity in cerebral cortex. Validating our classification scheme in vivo and matching ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

68
461
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 386 publications
(531 citation statements)
references
References 52 publications
68
461
1
1
Order By: Relevance
“…The CCK cells represent a large subset of excitatory interneurons, accounting for around a third of those in deeper laminae, and it is therefore not surprising that ablation results in a dramatic behavioral phenotype. Our findings, together with those of Häring et al (), suggest that CCK cells include functionally distinct subsets, such as those that co‐express PKCγ. The extensive overlap between CCK and PKCγ that we observed, taken together with earlier studies that have implicated PKCγ cells in neuropathic pain, raise the possibility that the CCK+/PKCγ+ cells may be particularly important for the development of mechanical allodynia.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The CCK cells represent a large subset of excitatory interneurons, accounting for around a third of those in deeper laminae, and it is therefore not surprising that ablation results in a dramatic behavioral phenotype. Our findings, together with those of Häring et al (), suggest that CCK cells include functionally distinct subsets, such as those that co‐express PKCγ. The extensive overlap between CCK and PKCγ that we observed, taken together with earlier studies that have implicated PKCγ cells in neuropathic pain, raise the possibility that the CCK+/PKCγ+ cells may be particularly important for the development of mechanical allodynia.…”
Section: Discussionsupporting
confidence: 83%
“…A recent transcriptomic study by Häring et al (2018) identified 15 classes of excitatory dorsal horn neuron, and their results are broadly consistent with the findings described above, as their classes include cells with high levels of the mRNAs for neurotensin, NKB, and substance P. Another peptide that featured in their classification scheme was cholecystokinin (CCK), which was expressed in three separate populations of excitatory neurons. Early reports had indicated that neurons with CCK mRNA were most numerous in lamina III and scattered through the other laminae (Abelson & Micevych, 1991;Cortes, Arvidsson, Schalling, Ceccatelli, & Hokfelt, 1990;Schiffmann, Teugels, Halleux, Menu, & Vanderhaeghen, 1991), while a recent study found that CCK defined a specific population of excitatory neurons in the deeper laminae of the dorsal horn (Abraira et al, 2017).…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Thus, more than 500 molecularly distinct classes of neurons and glial cells have been identified in the mouse brain [1,2], and information about the cellular composition of specific brain regions is increasing rapidly [2][3][4][5][6][7][8]. In addition, there is an even larger number of supporting glial cells, i.e., astrocytes and oligodendrocytes, the latter forming myelin sheets around neurons and making up a large part of the white matter in the brain.…”
Section: Introductionmentioning
confidence: 99%